Ases Pertimbangan MUI Dalam Pemberian fatwa Dalam Qaul Dhaif - M.Fikri Al Jundi; Abdul Malik Ibrohim; Muhibban (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
It is not uncommon for the MUI to use qaul dhoif in giving fatwas to people where the legal status of qaul dhoif is very weak in Islam. The aim of this research is to analyze the considerations of the Indonesian Ulema Council (MUI) in issuing fatwas that use qawa'id fiqhiyyah and hadith dhaif as a legal basis. The methods used in this research include a literature review of fatwas issued by the MUI as well as a qualitative analysis of the decision-making process in the social and cultural context of Indonesian society. The research results show that the MUI critically evaluates the quality and relevance of qaul dhaif before using it in a fatwa, taking into account aspects of the narrator's reliability, the connectedness of the sanad, and the consistency of the content with sharia principles. In addition, the use of qawa'id fiqhiyyah in MUI fatwas is not only limited to aspects of worship, but also covers contemporary issues, so that the resulting fatwa can provide relevant and useful guidance for society. This research underscores the importance of a cautious approach in the use of qaul dhaif to maintain the credibility of fatwas and encourage good deeds among Muslims.